Influence of the functional class of the players in wheelchair basketball: a comparative match analysis - Alsasua, R.; Arroyo, R.; Arana, J.; Lapresa, D.; Anguera, M. T. (Journal of Physical Education and Sport, 2021)
With the use of the observational methodology, a comparative match analysis has been carried out between the two finalist teams of the Paralympic Games in Rio de Janeiro 2016 -the observational sampling is made up of all the sequences finished in shooting in each of the matches played by the selections of USA and Spain-. The objective has been to characterize the way in which both teams resolve the issue of the functional class of their players and their influence on the construction of offensive sequences that end in a shot -effective and ineffective-. An adaptation (the introduction of the functional class handicap criterion) was performed on the observation instrument SOBL-2. Regarding the recording and coding process, the observation instrument has been introduced in the software LINCE. The reliability of the data has been guaranteed, in the form of inter- observer agreement, by means of the Cohen's Kappa coefficient. The results of the analysis of the search for associative relationships between categorical variables indicate how both selections solve the question of the functional class of their players in different ways; the Spanish team shows a game pattern that is further away from the results reflected in the scientific literature and the US game can be considered more orthodox. The T- patterns detected, using the THEME software (v.6 Edu), have made it possible to characterize sequences, effective and ineffective, common and differential in both teams, taking into account the functional class of the players who participate in the construction of the sequences that achieve a shot.